Plan de fidelización de clientes para Rosatel SAC. - Roncal Lázaro, Lenny Joana (2011)
The present research gathered the restlessness of how to implement an strategic plan of Customer relationship management and contribute to improve ROSATEL´s competitive positioning. Customer satisfaction is the key factor to identify the research´s problem. Only few media and virus marketing media was included as communication strategies. The research for ROSATEL allowed the application of knowledge acquired at Management Faculty in Universidad Nacional de Trujillo, during the process of study. The Hypothesis assumed is that a Customer Relationship Management would improve ROSATEL´s competitive positioning, analyzing independent variables given from the loyalty strategic plan and dependent variables (Rosatel´s positioning), which at same time is formed by: client satisfaction, barriers to change, rivalry, price, quality, value perception, image, confidence, security, availability, flexibility, compensation plan, after sells, location, innovation capability, service experience, concluding that Rosatel’s prestige is well known and has a competitive positioning which locate it as the sector leader with an inelastic demand (it doesn´t depend on Price, but brand) is blinding its business vision. In this scenario a several actions must be taken as promote a share vision, based on Customer Relationship Management where all Rosatel’s workers must be focus on. Lead this Project must consider integration activities between coworkers, implement CRM data base, to attract clients, spoil them, and achieve their loyalty with a POIN PROGRAM for Rosatel, maintaining surveillance on the competence offers, enhance Costumer service, encourage workers, not only with monetary incentives but with recognition as: medals, diplomas, events participation even with promotions. Furthermore, not forget social networks as facebook, twitter, etc. Achieving the comprehension and internalized this principles is for sure that ROSATEL will secure its position in Trujillo’s market.